Tense-lax contrasts in Indian English vowels: transfer effects from L1 Telugu at the phonetics-phonology interface - Payne, E; Maxwell, O; Volchok, B (Australasian Speech Science and Technology Association (ASSTA), 2019)
We investigate the effects of L1 Telugu on tense-lax contrasts in Indian English vowels. While English has a tense-lax contrast in high vowels, / iː, ɪ, uː, ʊ/, with duration as an additional cue, Telugu has only a shortlong contrast, /i, iː, u, uː/, though these also have the lax allophones /ɪ, ɪː, ʊ, ʊː/ as a result of vowel harmony (VH), triggered by a following low vowel. We examine whether L1 transfer effects are limited to the ‘base’ phonological inventory (e.g. ‘borrowing’ the Telugu length contrast for English), or whether speakers access the spectrally closer VH allophones from Telugu. The results reveal something more complex, with some speakers showing tense-lax allophones also for Telugu length contrasts. In L1-L2 transfer, these speakers exapt these phonetically laxer short allophones for the English lax vowels. The other speakers, showing less tense-lax variation all round in L1, create entirely new phonetic categories for the English lax vowels.